Learning Management System in Optimizing Distance and Independent Learning in Open High School - Winandar, Imam Zatnika; Rifandi, Ahmad (Journal of Innovation and Research in Primary Education, 2025)
Low student engagement and persistent negative perceptions of Open High Schools remain significant challenges in distance learning implementation. This study explores the use of Learning Management System (LMS) to enhance the effectiveness of distance and independent learning in Open High School contexts, specifically examining implementation strategies and their impact on student outcomes. A qualitative descriptive case study was conducted at SMA PGRI 31 Pangalengan, focusing on 108 working students unable to attend regular face-to-face learning among 412 total Open High School students. Data collection employed direct observation, in-depth interviews with key informants, and document analysis. The analytical framework followed Miles and Huberman's interactive model, incorporating George R. Terry's POAC management principles for systematic LMS implementation evaluation. LMS implementation achieved universal student participation (100%) across all class groups, representing a 22% increase from baseline participation rates of 78%. Academic performance demonstrated substantial improvement with Mid-Semester Summative Assessment scores increasing by 15.71%, from an average of 67.55 to 78.15 points. Implementation followed systematic phases including infrastructure development, comprehensive capacity building for educators and students, blended learning model integration, and activity-based monitoring. Primary challenges included limited internet connectivity, digital literacy barriers, and device availability constraints, which were addressed through strategic Wi-Fi provision, extended training programs, and community partnerships. The findings validate LMS effectiveness in addressing traditional distance learning challenges through systematic management approaches. Results align with contemporary educational technology literature emphasizing the importance of comprehensive institutional support, stakeholder training, and adaptive problem-solving in successful educational technology adoption. The study contributes empirical evidence supporting technology-enhanced open education as a viable alternative for students with geographical, economic, and social constraints while maintaining academic quality standards.